Pelaksanaan HIJAS di Pondok Pesantren MUS Candung - Sari Dewi; Deswalantri Deswalantri; Wedra Aprison; Fauzan Fauzan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
HIJAS is a school support program at the MUS Candung Islamic Boarding School. This research aims to determine the implementation of HIJAS and the values ​​that are instilled. Using qualitative methods, the key informant is the HIJAS coach as the implementer. Supporting informants: students and OSMUS as participants. Based on the results of observations and interviews, it is true that the HIJAS program instills religious values ​​such as: congregational morning prayers, discipline values, diligent recitation of the Koran and social.